When student teachers fail: perspectives of those in the ‘learning to teach’ partnership in the Republic of Ireland - Kilroy, Leo (2016)
In recent years there has been unprecedented international attention on the issue of teacher quality. This has resulted in a focus by policy makers on initial teacher education, with many systems opting to articulate standards to define the competences that newly qualified teachers should possess. Central to all programmes of initial teacher education is school placement, a key period of significant learning for student teachers and a time when their competence is assessed. A small proportion of student teachers experience failure or struggle during these placements, however little research into their experiences is evident. This qualitative study explores the perceptions and experiences of members of ‘triadic learning to teach partnerships,’ who have had experience of the phenomenon. In-depth, semi-structured interviews were used to capture data from student teachers, cooperating teachers, placement tutors and directors of school placement on their perspectives regarding the causes of student teacher failure, the impacts of its occurrence and the effectiveness of any support mechanisms provided. The findings revealed the complexity and uniqueness of each occurrence, and the significant impacts on all involved, most particularly the student teachers. Six typologies of student teachers who struggle or experience failure and five pillars for the provision of support emerged as new contributions to aid teacher educators to understand and adequately support these student teachers. Conclusions are also drawn regarding the need for a standards-led approach to the formulation of assessment judgements on student teachers’ competence and the need in the Irish context for cooperating teachers to be enabled to play a greater and more central role.